Ureaplasma Species Multiple Banded Antigen (MBA) Variation Is Associated with the Severity of Inflammation In vivo and In vitro in Human Placentae - Sweeney, Emma L.; Kallapur, Suhas G.; Meawad, Simone; Gisslen, Tate; Stephenson, Sally-Anne; Jobe, Alan H.; Knox, Christine L. (Frontiers in Cellular and Infection Microbiology, 2017)
Background: The multiple banded antigen (MBA), a surface-exposed lipoprotein, is a proposed virulence factor of Ureaplasma spp. We previously demonstrated that the number of Ureaplasma parvum MBA size variants in amniotic fluid was inversely proportional to the severity of chorioamnionitis in experimentally infected pregnant sheep. However, the effect of ureaplasma MBA size variation on inflammation in human pregnancies has not been reported. Methods: Ureaplasmas isolated from the chorioamnion of pregnant women from a previous study (n = 42) were speciated/serotyped and MBA size variation was demonstrated by PCR and western blot. Results were correlated with the severity of chorioamnionitis and cord blood cytokines. In vitro, THP-1-derived macrophages were exposed to recombinant-MBA proteins of differing sizes and NF-κB activation and cytokine responses were determined. Results: MBA size variation was identified in 21/32 (65.6%) clinical isolates (in 10 clinical isolates MBA size variation was unable to be determined). Any size variation (increase/decrease) of the MBA (regardless of Ureaplasma species or serovar) was associated with mild or absent chorioamnionitis (P = 0.023) and lower concentrations of cord blood cytokines IL-8 (P = 0.04) and G-CSF (P = 0.008). In vitro, recombinant-MBA variants elicited different cytokine responses and altered expression of NF-κB p65. Conclusion: This study demonstrates that size variation of the ureaplasma MBA protein modulates the host immune response in vivo and in vitro.